Electronic Spectral Studies on Pr3+ Doped Sulphonanilide System, Part II† - Tater, P.C.; Pandey, Aryamitra; Soni, K.P. (Asian Journal of Chemistry, 2010)
Nine sulphonanilides have been synthesised. Their interaction with Pr3+ ion in the form of doped model has been discussed in terms of Slater-Condon, Lande and Judd-Ofelt parameters. The involvement of 4f-orbitals in the Pr3+ doped systems including deviation in symmetry have been discussed.